The Concept of Industrialization and Structural Transformation in the Economy - M. Bagus Septia Budi; Muhammad Yasin (Escalate : Economics and Business Journal, 2026)
Industrialization and structural transformation are the main drivers of Indonesia's economic development, but the challenges of regional inequality and premature deindustrialization hamper inclusive growth. This study aims to analyze the role of technology in industrialization, its impact on socio-economic inequality, and the influence of structural transformation on economic growth. Using a qualitative descriptive approach through a systematic literature review, the population comprised indexed academic sources on Indonesian industrialization, with a purposive sample of 20-30 of the most relevant documents from 2021-2025. Secondary documents were analyzed through content analysis with source triangulation. The results show that technology improves production efficiency and human resource quality but widens inequality due to industrial concentration in Java and the emergence of the informal sector. Structural transformation has been slow, marked by a decline in the manufacturing contribution to GDP since 2013. In conclusion, technology-based inclusive policies are needed for sustainable growth.